2019
DOI: 10.1177/0165551519837187
|View full text |Cite
|
Sign up to set email alerts
|

An improved evidence-based aggregation method for sentiment analysis

Abstract: Sentiment analysis is one of the natural language processing tasks used to find reviews expressed in online texts and classify them into different classes. One of the most important factors affecting the efficiency of sentiment analysis methods is the aggregation algorithm used for scores combination. Recently, Dempster–Shafer algorithm has been used for scores aggregation. This algorithm has a higher precision than common methods such as average, weighed average, product and voting, but the problem with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…H2 is accepted. It is clear that the use of lexicon-based methods in the messages posted on Twitter allows us to establish the level of sentiment found in each of them, which is consistent with the studies of several researchers ( Wang et al, 2019 , Jamadi Khiabani et al, 2020 , Adwan et al, 2020 , Taboada et al, 2009 ). Likewise, as suggested by Mostafa and Nebot (2017) , it was found that the use of topic recognition techniques (classification of tweets by sociocultural factors) enables us to obtain a comprehensive understanding of the underlying causes of positive or negative sentiments.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…H2 is accepted. It is clear that the use of lexicon-based methods in the messages posted on Twitter allows us to establish the level of sentiment found in each of them, which is consistent with the studies of several researchers ( Wang et al, 2019 , Jamadi Khiabani et al, 2020 , Adwan et al, 2020 , Taboada et al, 2009 ). Likewise, as suggested by Mostafa and Nebot (2017) , it was found that the use of topic recognition techniques (classification of tweets by sociocultural factors) enables us to obtain a comprehensive understanding of the underlying causes of positive or negative sentiments.…”
Section: Resultssupporting
confidence: 84%
“…Actually, the study of the level of sentiment carried out in tweets allows us to compare the criteria of different researchers. Thus, it is demonstrated that thanks to the lexicon used in the tweets, we can understand specific ideas, judgments, concepts, and topics regarding the events of the COVID-19 pandemic ( Wang et al, 2019 , Jamadi Khiabani et al, 2020 , Taboada et al, 2009 ). In addition, when comparing the words used in the COVID-19 tweets and the list of words in the “Lexicom” dictionary that is embedded in the library (Sentiment Analysis) of the R program, we can confirm that the polarity score makes it possible to determine the positive, negative or neutral influence on the sentence ( Adwan et al, 2020 , Miao et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four evaluation criteria, namely precision (Pr), recall (Re), F1measure (F1), and accuracy (Acc), are used to assess the performance of the models. These criteria are extensively used in text classification and sentiment analysis tasks [23]. These criteria are calculated as follows:…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…The apps available in the store are downloaded by many users and Google Play Store users could comment on the desired application. Studies have demonstrated the reviews made by users on apps contains important information, including bug reports, feature requests and user experience of working with the app [3][4][5].…”
Section: Introductionmentioning
confidence: 99%